Information communication technology as an empowerment tool for the collective of women entrepreneurs - the case of the region Jaffna - Sri Lanka - Janani, T. (University of Jaffna, 2023)
The women headed families from north Sri Lanka are struggling for their livelihood and facing family's economic survival. They are trying to reduce their poverty level with the idea of small and medium enterprises (SMEs) because these are a major driver of employment growth and poverty alleviation in these countries. But their idea was not successful and not fulfilled their needs because of the lack of marketing facilities. Improving their marketing through online with the use of ICT as an empowerment tool for the group of women entrepreneurs, which has consisted of a series of workshops on digital media marketing through smartphones aimed at a group of women entrepreneurs whose ages were between 40 and 65 years old, from the Jaffna region in Sri Lanka. In this research the qualitative methodological paradigm and poverty reduction and knowledge improvement theory of the millennium goal were used. Data were collected from the participatory research methods and the researcher was a trainer and an observer. The research concluded that, using ICT as a tool for women's knowledge improvement is useful for poverty reduction and using ICT as a tool for empowerment and knowledge construction for marketing their products.
Keywords: Gender; Education; ICT; Empowerment; Women Entrepreneurs